Assessment of Nutritional Status, Body Composition and Blood Biochemical Parameters of Patients Following Sleeve Gastrectomy: 6 Months Follow Up - BATAR, NAZLI; Demir, Halime Pulat; Bayram, Hatice Merve (Elsevier, 2021)
Background and aims: Today, Sleeve gastrectomy (SG) has recently become the most common bariatric procedure among various bariatric surgical procedures due to its advantages. The aim of this study is to investigate nutritional status, body composition and biochemical parameters following SG. Methods: This was a prospective study, the subjects were patients who underwent SG at a special obesity clinic in Istanbul, Turkey, between 01.05.2017 and 01.11.2017. The mean body mass index (BMI) of the participants was 42.15 +/- 4.84 kg/m(2) for men and 41.44 +/- 4.34 kg/m(2) for women, preoperatively. Nutritional status, some anthropometric measurements and blood sampling were taken at each visit. Data were collected and analyzed for the present study at the following periods: pre-operation (pre-op), 1 month, 3 months and 6 months after surgery. Results: A total of 47 SG patients (20 men, 27 women) were evaluated. The mean BMI was 30.23 +/- 3.56 kg/m(2) for men and 30.35 +/- 4.36 kg/m(2) for women after 6 months and the amount of excess weight loss (EWL) increased in the 3 months (p <.001). Mean energy, fiber, vitamin A, vitamin C, vitamin B-1, niacin, vitamin B-12, folate, calcium, magnesium, iron, zinc, phosphorus and iodine were above the Dietary Reference Intake (DRI) recommendations. A significant association was found between protein intake and fat free mass loss in both genders after SG at 6 months (p <.05). Conclusion: Nutrition deficiencies are common for patients after SG. Therefore, it is important to routinely monitor these patients with a professional team. (C) 2021 European Society for Clinical Nutrition and Metabolism. Published by Elsevier Ltd. All rights reserved.
Keywords: Bariatric Surgery; Obesity; Nutritional Status; Body Composition; Biochemical Parameters